Evaluation of a portable mixer and feed delivery system - C R Stark; Robert D Goodband; Keith C Behnke (Kansas Agricultural Experiment Station Research Reports, 1991)
An on-farm mixer uniformity study was conducted to determine if feed could be properly mixed and maintained as it went through a bulk bin and conveying equipment over a distance of 180 ft. in a grower-finisher facility. A portable vertical mixer was tested and found to produced a uniformly mixed feed. Uniform feed was then conveyed from a bulk storage bin to feeders inside the facility. Samples were obtained from three different feeders and were tested for uniformity. Results indicate that feed remains uniform as it is conveyed and deposited in feeders over distances of 20, 80, and 180 ft.; Swine Day, Manhattan, KS, November 21, 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; On-the-farm feed manufacturing; Portable mixers